PERAN GURU YANG PROFESIONAL DALAM PEMBENTUKAN NILAI-NILAI KARAKTER DI SEKOLAH - HOTMAULINA SIHOTANG (FIP Unimed, 2013)
ABSTRACT This article’s purpose is giving solution to the problem how teacher role to build and develop the caracter of the students in school. Character education is a system of cultivation of character values ​​to students . The values ​​in education are : (1) religious ; (2) to be honest ; (3) tolerance ; (4) discipline ; (5) hard work ; (6) creative ; (7) independently ; (8) democratic ; (9) curiosity ; (10) the national spirit ; (11) love of country ; (12) reward achievement ; (13) make friends / communicative ; (14) love peace ; (15) likes to read ; (16) care about the environment ; (17) social care ; and (18) responsibility . Character building is influenced by the environment at home , at school , in the community . Character building values ​​through character education is a very important and strategic in building a national identity and mobilize the formation of a new Indonesian society . Therefore , the first step is a relationship (educational networks ) between the family , school, and environments . As a professional school teacher who has a strategic role to build character and character of students is not done solely through the learning of knowledge , but also through values ​​education. Keywords : professional teachers , character values